Kepentingan Stakeholder dalam Perumusan Kebijakan (Studi Kasus Perda Rt Rw Provinsi Riau No 10 Tahun 2018) - Syahri Ramadhani Sinuraya; Ali Yusri; Muchid Muchid (Journal on Education, 2022)
The purpose of this study is to see how the roles and interests of stakeholders in a policy. Riau Province Regional Spatial Planning Regulation No. 10 of 2018 is a policy that is really needed by the Riau Provincial Government, especially in an effort to regulate how the spatial planning of areas and land in Riau Province should be. The large number of actors involved in the formulation of the Regional Regulation on Regional Spatial Planning for Riau Province resulted in the formulation process taking quite a long time and this became the author's analysis for formulating research problems. Based on the results of stakeholder identification, it shows that there were 9 stakeholders involved in the process of formulating the Riau Province Regional Regulation on Regional Spatial Planning, both at the national and regional levels, consisting of four key stakeholders who were all from central government agencies, two main stakeholders consisting of government agencies. regions, and two supporting stakeholders consisting of Non-Governmental Organizations and Corporations. Analysis of the interests and influence of stakeholders involved in the process of formulating the Regional Regulation on Regional Spatial Planning for Riau Province was categorized based on the level of interest and influence, namely the Ministry of Environment and Forestry and the Ministry of Home Affairs which were included in the key player category from the results of the analysis. Then the Ombudsman and the Ministry of Public Works are included in the context setters category, and the last is the subject category which includes the Riau Provincial Government, the Riau Provincial DPRD, Walhi, Jikalahari, and corporations whose land is included in the forest area in the Regional Regulation on the Riau Province RTRW